Demographic Influences on Investment Behavior: Analyzing the Role of Age, Gender, and Education - Shah, Nirmit; Shah, Hitarth; Thakkar, Krish; Guha, Tannay; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This study examines the demographic characteristics of respondents - age, gender, and education—and their influence on investment behaviors. The sample is predominantly young, with 68.3% aged 18-25, and shows a male skew (56.7%). Most participants hold undergraduate degrees (53.8%), indicating a highly educated demographic. The analysis reveals significant differences in investment experience, risk tolerance, and financial planning priorities based on these factors. Younger respondents demonstrate higher risk tolerance, while gender differences highlight varying approaches to financial planning. The study’s findings contribute to understanding how demographic factors shape investment strategies, with global implications for financial markets. Future research should include more diverse age groups, gender balance, and cross-cultural comparisons to enhance the global understanding of investment behaviors.